2015
DOI: 10.1103/physrevc.91.064901
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the shear viscosity at finite net-baryon density fromA+Acollision data atsNN=7.7200GeV

Abstract: Hybrid approaches based on relativistic hydrodynamics and transport theory have been successfully applied for many years for the dynamical description of heavy ion collisions at ultrarelativistic energies. In this work a new viscous hybrid model employing the hadron transport approach UrQMD for the early and late non-equilibrium stages of the reaction, and 3+1 dimensional viscous hydrodynamics for the hot and dense quark-gluon plasma stage is introduced. This approach includes the equation of motion for finite… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
165
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(176 citation statements)
references
References 65 publications
(65 reference statements)
11
165
0
Order By: Relevance
“…In contrast to v n , the excitation function of the viscous parameter β " shows a non-monotonic behaviour over the same beam energy range. A similar non-monotonic trend for η/s has been observed in the hybrid viscous hydrodynamical calculations [28], tuned to describe the STAR BES-I v 2 data.…”
Section: Search For the Turning Off Of The Signatures Of The Qgpmentioning
confidence: 50%
“…In contrast to v n , the excitation function of the viscous parameter β " shows a non-monotonic behaviour over the same beam energy range. A similar non-monotonic trend for η/s has been observed in the hybrid viscous hydrodynamical calculations [28], tuned to describe the STAR BES-I v 2 data.…”
Section: Search For the Turning Off Of The Signatures Of The Qgpmentioning
confidence: 50%
“…In figure 1, the comparison between the hydrosolver+UrQMD [21] [23]. Within the analyzed range, the CERES v 3 does not show centrality dependence [22].…”
Section: Resultsmentioning
confidence: 99%
“…In Ref. [19], the authors of the hybrid model investigated parameter dependence of the model results in the case of 0-5% centrality AuAu collisions at √ s NN = 19.6 GeV. It is shown that the model results change less than 10% when the parameters of the model are varied by 10%.…”
Section: Epj Web Of Conferencesmentioning
confidence: 99%
“…Within it, kinetic and chemical freeze-outs are described dynamically by the UrQMD hadron cascade without a unique freeze-out temperature. The transition from fluid to cascade part, so called the 'particlization' [19], is set to take place on a constant energy density surface with = 0.5 GeV/fm 3 . But, as the net baryon density is not uniform on such a surface, this density does not correspond to a single temperature.…”
Section: Epj Web Of Conferencesmentioning
confidence: 99%
See 1 more Smart Citation